FAMILY ALLOWANCE FOR SOCIAL CHILD PROTECTION – REFERRAL TO THE RIGHT TO CHILD ALLOWANCE (Annual of the Faculty of Philosophy in Skopje, 2019)
Family allowance for social protection of children is defined in the Law onProtection of Children, as follows: children allowance, special allowance, single financialassistance for a new-born child and parental allowance for a child. The thesisdeals with the most common social financial assistance for the family with childrenand their right to child allowance.Most often, the child allowance is granted to all families whose total familyincome is below a certain financial threshold and is designed to help cover the costsof supporting a child to a certain age. Sometimes this right is conditioned by the employmentof parents, schooling of children, vaccines and health examinations.The European Union Law prescribes that child’s allowances/benefits of thechild allowance are taken over the country of residence where the EU citizen lives orworks, regardless of the nationality. Thus, by applying the comparative method, thethesis makes an overview of the realization of the right to child allowance in some ofthe EU countries.Using the legal and sociological method, an analysis of the right to child allowancein the Republic of North Macedonia is also elaborated.Further in the thesis, a combination of quantitative and qualitative researchmethods is used, analysing secondary data. The main instrument used in the thesisanalysis is the critical review of the applicable legislation concerning the right tochild allowance and the system of social protection of children.